Modelling of 2,4-dichlorophenol, an emerging pollutant removal from water by adsorption onto sugarcane bagasse biochar using response surface methodology - Tapas Paul; Rishika M S; Bhautik D. Savaliya; Saurav Kumar; Pritam Sarkar; Prasenjit Pal; S.P. Shukla; Kundan Kumar; Ashish Kumar Jha; Ganesh Kumar; Supratim Malla (Journal of Fisheries, 2026)
This study evaluated the potential of sugarcane bagasse biochar as a low-cost adsorbent for removing 2, 4-dichlorophenol (2, 4-DCP), an emerging pollutant from water using adsorption modelling and response surface methodology. It aimed to determine optimal combinations of concentration, contact time, pH and dose for maximizing contaminant uptake in batch and column systems. Batch adsorption experiments were planned using a Box–Behnken response surface experimental design with initial 2, 4-DCP concentration (25, 50, and 75 mg L–¹), contact time (20, 40, and 60 min), solution pH (5, 7, and 9), and biochar dosage (6.25, 12.5, and 25 mg). Fixed-bed column studies were conducted under continuous flow to assess dynamic performance and breakthrough behaviour. Adsorption equilibrium, kinetics and column behaviour were analysed using standard isotherm and kinetic models, supported by surface and functional-group characterization. The optimized batch conditions produced removal efficiencies of about 95% with high monolayer adsorption capacity on a homogeneous biochar surface. The equilibrium data followed a monolayer adsorption model, while kinetic analysis indicated rapid uptake controlled primarily by surface-site availability. Column studies showed high dynamic capacity and well-defined breakthrough characteristics under the tested flow conditions. Sugarcane bagasse biochar proved to be an efficient and technically suitable material for removing phenolic contaminants such as 2, 4-DCP from water. The findings demonstrate a productive use of agro-industrial waste for water purification and support its application in practical treatment units for removing emerging pollutants in aquatic environments.